Learning Malay online at tertiary level -regular paper - Sew, Jyh Wee (Penerbit UKM, 2012)
This is a discussion on technology assisted language learning at tertiary level that delimits blogging as a form of e-learning for enhancing foreign language acquisition. Examining the dynamics, rather than the outcomes, behind the integration of weblog as part of a Malay module puts the spotlight on the efficacy of blogging in developing Malay literacy. The reflections of the tertiary learner blogging Malay as a literacy development are presented for c nsideration towards practical internet-based pedagogy in line with Y generation’s current social-interactive practice. One observation derivable from blogging Malay literacy, i.e. developing written Malay proficiency with online journaling, is that a foreign language learner may learn collaboratively by tapping on the overlapping techniques of decoding and encoding a target language online at the intersection of cognitive-digital interface. The interactivity suggests that diversified stimulation is required in e-learning pedagogy not least foreign language acquisition involves multi-faceted cognitive, verbal, and auditory coordination. It is observed that digitalized asynchronous interaction contains synchronous learning stimulations,especially from the repeated viewing of the digital social media incorporated into the blogging practice. Arguably, educational social technology, in the form of embedded YouTube video clips in the weblogs, offers a foreign language learner with an affordance to generate a simulated face-to-face interactivity serving as a useful scaffold to improve foreign language proficiency. Applying the weblog to learn Malay, in turn, amplifies the cognitive receptiveness on the learner’s part, which is an advantage of introducing and maintaining a collective of diverse learning stimulation in accommodating foreign language learning.